Effects of Parental Involvement on Pre-schoolers Academic Performance: A Case Study of Some Selected Schools in Jigawa State, Nigeria - Muhammad, Halima Umar; Ibrahim, Baffa Bashari; Abdullahi, Auwalu; Ringim, Iliyasu Ibrahim (CV. Srikandi Kreatif Nusantara in collaboration with Institut Teknologi Mojosari Nganjuk, 2025)
The essence of education in human life is very emphatic. Education or training of human in the course of life begins formally at a stage known as preschool, where kids are enrolled to be coach about the upcoming requirements of life and learning. The significance of this level of learning or training called early childhood education or care is very impressive. Therefore, this study was carried out to investigate the effects of parental involvement on the academic performance of preschoolers in some selected schools in Ringim Local Government Area, Jigawa State, Nigeria. In terms of methods, a total of 30 preschoolers were selected, therewith, divided as two study groups: Group A (test group) and Group B (control group). Therein, the results revealed that, the children who had previously received parental involvement (according to their records) scored higher mean marks (1009 ± 49) compared to those children who did not receive parental involvement (617 ± 26). In light of the revealing from the findings, it can be concluded that, indeed parental involvement has a significant impact on the academic performance of preschoolers. Ways of ensuring that parent pay more attention to their children at preschools or early child care education shall be devised.